Socio-temporal contextual and community factors associated with daily exclusive ENDS use and dual use with tobacco cigarettes among adolescent vapers: an ecological momentary assessment study - Melissa H. Abadi; Stephen R. Shamblen; Kirsten Thompson; Sharon Lipperman-Kreda; Joel Grube; Bonnie O. Richard; Camila Aramburu (BMC, 2022)
Abstract Background Adolescents who dual use ENDS with tobacco cigarettes are more likely to have an increased risk of developing dependence. Yet, little is understood about the factors driving dual use among adolescents. The current study sought to reveal the day-to-day socio-temporal contextual and community factors associated with adolescents' use of electronic nicotine delivery systems (ENDS), and how these factors predict dual use with tobacco cigarettes. Methods We collected ecological momentary assessments (EMA) from a sample of 50 adolescent past two-week vapers (ages 14-17 years old) over 14 days. Daily EMA data were collected on ENDS and tobacco cigarette use, as well as a range of contextual (i.e., motivations to vape, location of vaping, who with when vaping) and community factors (i.e., exposure to peers vaping, to adults vaping, to ENDS advertising, to ENDS warning messages). Our primary analyses were multilevel regressions, accounting for daily observations nested within individuals (N = 700 observations). Results Participants used ENDS exclusively on 44% of days and dual used ENDS and tobacco cigarettes on 8% of the days. Dual use days (versus exclusive ENDS use days) were associated with "vaping because tobacco use was prohibited" (OR = 34.65, p < .05). Also, dual use days (versus no use days) were associated with greater exposure to adults vaping (OR = 5.59, p < .05), peers vaping (OR = 7.48, p < .05), and (c) ENDS advertisements or promotions (OR = 2.12, p < .01), whereas exclusive use days (versus no use days) were only associated with greater exposure to peers vaping (OR = 2.58, p < .01). Conclusions Results showed that exposure to peers and adults vaping and exposure to ENDS marketing were associated with same day dual use behaviors. And, that adolescents who dual used were motivated to use ENDS because they were easy to conceal. Findings support stricter regulation of ENDS marketing and for smoke-free air laws that include ENDS. In addition, these findings support prioritizing family- and school-based prevention programming that effectively communicates risk associated with ENDS use, including heightened risk of dual use and dependence. Such efforts can reduce the number of adolescents who use ENDS as well as the number who transition to tobacco cigarette use.